The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5301/ejo.5000132
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal hematoma after canaloplasty and clear cornea phacoemulsification: surgical management

Abstract: This operation was a minimally invasive technique to remove intrastromal hematocornea after viscocanaloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…While dilating Schlemm canal with viscoelastics, a detachment of Descemet membrane may occur. An intracorneal hematoma is a rare complication following Descemet detachment and can be removed by partial-thickness paracentesis [22]. Descemet detachment was not encountered in our study.…”
Section: Discussionmentioning
confidence: 58%
“…While dilating Schlemm canal with viscoelastics, a detachment of Descemet membrane may occur. An intracorneal hematoma is a rare complication following Descemet detachment and can be removed by partial-thickness paracentesis [22]. Descemet detachment was not encountered in our study.…”
Section: Discussionmentioning
confidence: 58%
“…The same concept may be applied to monitor the effects of minimally invasive nonpenetrating glaucoma procedures and implantation of devices designed to bypass the trabecular network. [23][24][25][26][27][28][29][30] Cadaveric models suggested that TM expansion into SC would be observed with IOP elevation. 15 Mathematical modeling of the outflow system also predicts compression of SC in response to IOP elevation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition, these conditions are associated with similar insults to the cornea such as corneal grafting, infection, inflammatory corneal diseases, intraocular surgery, extraocular surgery, ocular trauma, and, in human beings, contact lens irritation. [7][8][9] In many cases, ICH resolves spontaneously over time with or without the use of specific topical treatments. 2,10 According to literature describing human ICH, severe cases may require surgical drainage of the hemorrhage or corneal transplantation to salvage normal function of the eye.…”
Section: Introductionmentioning
confidence: 99%